Antioxidant properties of the three different varieties of cassava (Manihot esculenta Crantz) leaves. - Pormilda, Gracechel Ann C. (2019.)
Leaf extracts of the three varieties of cassava (Manihot esculenta Crantz), namely, Lakan-1, Java, and KU-50, were studied for their antioxidant activities. The samples were collected, cut to pieces, powdered then transferred in a container containing methanol. The methanolic extracts were filtered and subjected to rotary evaporation. The concentrated extracts were then subjected in a DPPH free radical scavenging assay. The KU-50 extract exhibited the highest activity at 68.4± 1.8%, comparable to that of the positive control (ascorbic acid) and is significantly higher than the other extracts. The extract that showed the highest antioxidant activity was subjected to phytochemical screening to determine any presence of secondary metabolites. Alkaloids, phenols, saponins, and tannins were found to be present in the extract of the KU-50 variety. The results for the evaluation of the DPPH radical scavenging assay and phytochemical screening of the extract from the KU-50 variety of cassava suggest that the said variety can be processes and used in the medicinal field due to its antioxidant activity.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Cassava; Manihot esculenta Crantz